Chile : 2009 Article IV Consultation; Staff Report; Staff Statement and Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Chile. (IMF Staff Country Reports; Country Report ;, 2009)
This 2009 Article IV Consultation highlights that the Chilean economy has proved resilient in the face of the global financial crisis. The policy response to the crisis has been sizable, well balanced, and coordinated. Executive Directors have commended the Chilean authorities for their sound policy framework underpinned by an inflation target regime, a structural budget rule, and a flexible exchange rate regime. Directors have also endorsed the Central Bank of Chile's decision to implement alternative means of monetary easing to support activity and a return of inflation to the target.